(3GdENJdGLs - (3GHf SjQjf , eMeO Hf SjQjf GdHUQj GdCfUGQj, CHh HcQ,J (B110 (3g` s
(3ChdgG (B:s
(3PcQ GdENJdGL dGHf YHO Gddg eMeO Hf SjQjf eG jchf ai GdQCS EPG ENJdL GdjGahL s
(3BNQgG (B:s
(3HGH GdEdjJjf EPG ENJdLJ Gdjefi hjONd Ydjg ef MjK dG jYde hGddg CYde ced cJGH GdENJdGL HMeO Gddg hMSf Yhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B154 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B59s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3?(B) s
Keywords: (3GdeLGejYs